Turf wars : territory and citizenship in the contemporary state - Ng'weno, Bettina (Stanford University Press, 2007)
People of African descent living in the Colombian Andes had long been struggling, as peasants and workers, for political participation and equal citizenship. When the 1991 Colombian Constitution enabled them to claim territory as ethnic groups, their demands became part of a growing worldwide phenomenon of citizenship claims that are based on territory and expressed through cultural distinction. This book looks at two such claims pursued by Afro-Colombians in the 1990s and investigates how territory serves to connect and disconnect citizen and state in the context of today's changing state authority, legitimacy, and institutions.